A Review: Induced Pluripotent Stem Cells (iPS) Therapy Is the Best Method to Cure Non-Communicable Diseases? - Yola Eka Erwinda (Badan Pengawas Obat dan Makanan, 2020)
The potency of stem cells in treatment or therapy is widely known due the properties of stem cells to differentiate into specialized cell type in the body. Application stem cells in medicine and therapy is mostly used for alternative treatment of diseases that could not be cured using chemical or other biological drugs, such as non-communicable diseases. In general, stem cells are classified in three types, namely Adult Stem Cells (ASC), Human Embryonic Stem Cells (hESC), and Induced Pluripotent Stem Cells. Each type of the cells has advantages and drawbacks for application in medicine and therapy. This review investigates whether iPS is the best approach for non-communicable disease treatment among other stem cell types.